Modelling Innovation Contribution to Economic Growth of Industrial Regions - Kharazishvili, Yurii; Kwiliński, Aleksy; Dźwigoł, Henryk; Dźwigoł-Barosz, Mariola (<center>Conference Proceedings Determinants Of Regional Development</center>, 2021)
The article considers approaches to determining the innovative contribution to economic growth and economic development. Attempts to make such a determination in the known studies are limited by using methods of: integrated estimation, expert evaluations, multipliers, econometric models. Most of the considered approaches are focused on identifying the innovative impact on economic development, rather than on economic growth. It is proposed to expand the Cobb-Douglas production function by including, in addition to STP, labour costs and capital costs, as well as an innovation factor, which includes: gross domestic R&D expenditures, innovation expenditures, and total education expenditures. To determine the contribution of the innovation factor to economic growth, the "Solow balance method" is used, which, through logarithmization and obtaining logarithmic derivatives in the production function, allows obtaining formalized information about each factor's contribution to economic growth and developing necessary regulatory measures. The method is universal and can be applied to any country, region or type of economic activity.